2020
DOI: 10.3390/jpm10010005
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Microscopic Structures of Human Dental Enamel Can Predict Caries Experience

Abstract: Objectives: The hierarchical structure of enamel gives insight on the properties of enamel and can influence its strength and ultimately caries experience. Currently, past caries experience is quantified using the decayed, missing, filled teeth/decayed, missing, filled surface (DMFT/DMFS for permanent teeth; dmft/dmfs for primary teeth), or international caries detection and assessment system (ICDAS) scores. By analyzing the structure of enamel, a new measurement can be utilized clinically to predict susceptib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Before etching, the enamel is polished and cleaned. However, a large amount of protein remains on the enamel surface after polishing [ 25 ]. The degree of enamel demineralization after acid etching varies because of different degrees of mineralization on the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Before etching, the enamel is polished and cleaned. However, a large amount of protein remains on the enamel surface after polishing [ 25 ]. The degree of enamel demineralization after acid etching varies because of different degrees of mineralization on the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase 2, also known as gelatinase A, is a membrane-bound protein with collagen-degrading ability [20,22] and has important roles in tooth formation and mineralization [23][24][25][26][27]. Genetic polymorphisms in enamel formation genes could contribute to structural alterations that could lead to enamel porosity, presence of enamel crystal inhibitory proteins and decreased mineral content [21,28,29]. Some studies have demonstrated the expression of MMP2 during enamel formation [23][24][25].…”
Section: Plos Onementioning
confidence: 99%
“…We and others have hypothesized that variation in enamel formation genes could explain in part individual susceptibility to dental caries (1,3). Further, genetic variation in amelogenin was associated with caries experience (4-11), erosive tooth wear (12), variation in microscopic enamel structure (13), salivary calcium levels (14), and molar-incisor hypomineralization (MIH) (8) in a number of cohorts with distinct geographic origins, and with incisor enamel microhardness in amelogenin-impaired mouse models (15).…”
Section: Dental Caries Epidemiologymentioning
confidence: 99%